55. Selective stimulation of A delta fibres by micropatterned interdigitated surface electrodes. Issue 4 (April 2016) - Marinelli, L.; Pellegrino, L.; Siri, A.; Leandri, M.
Abstract : Electrophysiological assessment of the nociceptive pathway is a difficult task, just recently accomplished by laser stimulators, which only activate pain endings. Unfortunately, there are several drawbacks to this type of stimulus, for its costly generator, for the possible skin lesions and difficult handling. Electric stimuli are far more easy to generate and deliver, but they lack the necessary selectivity. We demonstrate here that by using a bipolar comb like electrode where multiple rails of opposite polarity are only distant 50 μm (Pat. No. I0158846), selective activation of a sufficient number of nociceptors pertaining to the A delta range is possible. In 5 healthy volunteers, the radial nerve innervation territory was stimulated with 1 ms pulses delivered through the electrode; recordings were performed from the radial nerve above the wrist, with near nerve needles. Sensory nerve potentials could be recorded with conduction velocity ranging 12–20 m/s, compatible with A delta fibres. Increasing the electrode inter rail distance up to 200 μm and stimulating the same site brought an increase of conduction velocity up to 42 m/s, in the range of A beta fibres.